2009
DOI: 10.1007/s00280-009-1118-2
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab induced reversible thrombocytopenia in a patient with recurrent high-grade glioma: a case report

Abstract: We report a case of bevacizumab (BEV)-induced thrombocytopenia in a 36-year-old woman treated with BEV as a single-agent for a recurrent high-grade glioma. The thrombocytopenia was both reversible and reproducible on multiple treatment cycles. The patient has improved clinically and by brain MR imaging with single-agent BEV for approximately 7 months to date. She did not have bleeding or thromboembolic complications. Treatment delays have been 1-2 weeks relative to a conventional plan of treatment, i.e., 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thrombocytopenia is a rare adverse effect of BEV that has only few case reports in the literature. Leal et al reported a case of bevacizumab-induced reversible thrombocytopenia in a patient with recurrent high-grade glioma [4]. In their case report, the patient had no bleeding and platelet count was mildly dropped, but our patient had melena, epistaxis with severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 58%
“…Thrombocytopenia is a rare adverse effect of BEV that has only few case reports in the literature. Leal et al reported a case of bevacizumab-induced reversible thrombocytopenia in a patient with recurrent high-grade glioma [4]. In their case report, the patient had no bleeding and platelet count was mildly dropped, but our patient had melena, epistaxis with severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 58%
“…Bevacizumab administration has been associated with thrombocytopenia and thrombosis in human trials but not nonclinical safety studies (Leal and Robins 2010;Scappaticci et al 2007). Postulated mechanisms include platelet consumption due to endothelial dysfunction from lack of VEGF (Kilickap, Abali, and Celik 2003), a HIT-like mechanism, and direct effects on platelet life span.…”
Section: Bevacizumabmentioning
confidence: 99%
“…Immune-mediated thrombocytopenia can occur as a result of drug-induced antibody formation against platelets, leading to their destruction [11]. Reports on this rare adverse event have been published [3,8,12]. However, in this particular case, laboratory findings did not provide definitive evidence indicating immune-mediated thrombocytopenia, such as In this panel, photographic captures (a-d) of the patient's digestive endoscopy are presented, showing multiple angiodysplasias.…”
Section: Discussionmentioning
confidence: 96%